Householders as designers? Generating future energy services with United Kingdom home occupiers. (November 2020) - Cockbill, Stuart A.; Mitchell, Val; May, Andrew J.
Highlights: Householders were immersed in their world of energy data for one year. Eleven service concepts developed were generated using a co-design approach. Services comprised: 'information tools', 'control tools', and 'game changers'. Traditional explicit energy feedback did not figure highly in these services. Key challenges were providing meaning, building trust and ensuring data privacy. Abstract: The increasing adoption of smart meters and smart home technologies in domestic dwellings affords new opportunities to collect data about householders' everyday lives, including their energy use. Current services designed to support householders in reducing their energy use predominantly push 'feedback' at householders with limited effect. New services are needed that better engage householders with their energy data and energy saving options in more meaningful ways, and/or facilitate broader energy saving behaviours. After householders had spent a year being immersed in their energy data, this study used a co-design approach with householders, researchers, designers and building energy technologists to generate a set of future energy-related services that would benefit householders. The results present 11 co-designed concepts for future services that support householders in making structural and behavioural changes around energy use, alongside concepts that use energy data to impact positively on future lifestyles. Opportunities, challenges and the implications for the design of future energy services are then discussed. The article closes with reflections on the role of the collaborative design approach used to generate these visions of the future.